PENGARUH GREEN PRODUCT DAN GREEN PROMOTION TERHADAP BRAND IMAGE PT SUZUKI INDOMOBIL DI KOTA PADANG - Dio Findi Priyanka (Universitas Negeri Padang, 2019)
This research aims to examine: (1) the influence of green product against PT Indomobil Suzuki brand image in the city of Padang, and (2) the influence of green promotion against PT Indomobil Suzuki brand image in the city of Padang. Type of this research is quantitative research analysis techniques, using korelasional, which is the population in this research is the entire consumer users of Suzuki in Padang city of unknown amount. Researchers took samples of as many as 100 people. Sampling technique used was purposive sampling technique. The type of data in this study are the primary and secondary data. Primary data obtained by spreading the now's research. Technique of data analysis is the analysis of descriptive and Inductive analysis. Test the hypothesis in this study was conducted with the test t (t-test). The results of this research show that: (1) Green Product has the insignificant effect towards the brand image, (2) Green Promotion has the significant effect towards brand image.Keywords: Brand Imageg, Green Product, and Green Promotion.